2020
DOI: 10.1111/jnc.14987
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and neurogenesis alterations in Alzheimer’s disease and diabetes mellitus mixed murine models

Abstract: The classic neuropathological features of Alzheimer's disease (AD) are accompanied by other complications, including alterations in adult cell proliferation and neurogenesis. Moreover recent studies have shown that traditional markers of the neurogenic process, such as doublecortin (DCX), may also be expressed in CD8+ T cells and ionized calcium‐binding adaptor molecule 1 (Iba1+) microglia, in the close proximity to senile plaques, increasing the complexity of the condition. Altered glucose tolerance, observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Brain damage caused by neurological and vascular disorders or by traumatic injuries is tightly associated with an irreversible neuronal loss, which may lead to cognitive impairment, motor dysfunction, and even alterations of the personality. Despite the physiological capacity of the adult brain to generate new neurons from neural stem cells (NSC) in the subventricular zone (SVZ) and the dentate gyrus (DG) of the hippocampus, neuronal replacement in damaged brain regions rarely occurs, complicating functional recovery. An association of alterations in neurogenesis with cognitive impairment has been described in mouse models of different metabolic and neurological disorders, , and it is generally accepted that increased neurogenesis leads to improve cognitive performance . Thus, this field demands the discovery of new drugs that regenerate damaged brain regions, facilitating functional recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain damage caused by neurological and vascular disorders or by traumatic injuries is tightly associated with an irreversible neuronal loss, which may lead to cognitive impairment, motor dysfunction, and even alterations of the personality. Despite the physiological capacity of the adult brain to generate new neurons from neural stem cells (NSC) in the subventricular zone (SVZ) and the dentate gyrus (DG) of the hippocampus, neuronal replacement in damaged brain regions rarely occurs, complicating functional recovery. An association of alterations in neurogenesis with cognitive impairment has been described in mouse models of different metabolic and neurological disorders, , and it is generally accepted that increased neurogenesis leads to improve cognitive performance . Thus, this field demands the discovery of new drugs that regenerate damaged brain regions, facilitating functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The phorbol-containing fraction (Fr4) was purified by open-column chromatography using hexane/EtOAc (30:70−0:100, v/v) to obtain four subfractions which were analyzed by UHPLC−HRMS, taking into account the results of mass spectroscopy of our synthetic phorbol 12,13-diesters. A compound isomeric to phorbol 12-phenylacetate-13isobutyrate (7) was detected in subfraction FR4-4 (58.1 mg), which was further chromatographed through analytic HPLC using Si-60 column and EtOAc/hexane (40% of EtOAc) as the solvent system. Finally, two compounds not described previously, 12-deoxy-16hydroxyphorbol 13-phenylacetate-16-isobutyrate (DPPI, 10, 1.0 mg, 0.0005%, 46.18 min) and 12-deoxy-16-hydroxyphorbol 13-phenylacetate-16-tigliate (DPPT, 11, 1.4 mg, 0.0007%, 51.1 min), were isolated.…”
mentioning
confidence: 99%
“…Furthermore, previous studies conducted in mouse models showed that worse metabolic conditions correlate with lower rates of central cell proliferation, increased neurogenesis rates, and progress in cognitive impairment [65,66]. It has been observed that during youth, the body system tries to compensate the generation of new neurons in young mice, but this ability is diminished in adults and the elderly, especially in the presence of a dementia such as AD [67]. Human studies have shown a similar trend and suggest that obesity and AD share the same neurodegenerative mechanisms, promoting in turn, an acceleration of the degenerative process at the central level [68].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, it has been shown that an imbalance in insulin levels also impairs neurogenesis in early life [ 107 ], as well as in more mature and long-lived phases [ 37 ]. In addition, the coexistence of T2D with AD pathology reduces neurogenesis and thus neuronal replacement from stages prior to cognitive decline [ 126 ]. Insulin is also involved in the regulation of neuronal and synaptic functions in the hippocampus, cortex and cerebellum, protecting neurons from neurodegeneration and cell death [ 127 , 128 , 129 , 130 ].…”
Section: Link Between Diabetes Mellitus Alzheimer’s Disease and Vascu...mentioning
confidence: 99%